Pengaruh Ukuran Perusahaan, Tangibility, Likuiditas dan Profitabilitas terhadap Struktur Modal pada Perusahaan Industri Pertambangan Batu Bara - Alya Syafi Rifiana; Eka Febiyanti; Hersugondo Hersugondo (Universitas Wahid Hasyim, 2021)
This study aims to determine the effect of company size, tangibility, liquidity and profitability (ROA and ROE) on capital structure. This research uses quantitative research methods. This type of research is descriptive statistical research and the nature of this research is a causal relationship which explains the causal relationship between the independent variables and the dependent variable. This research was conducted at coal mining companies listed on the Indonesia Stock Exchange in 2014-2019. The sample in this study was 19 coal mining companies listed on the Indonesia Stock Exchange in 2014-2019. The analysis tool used is multiple linear regressions. The result of this research is that partially company size and liquidity have no effect on capital structure. Tangibility and return on equity (ROE) have a positive and significant effect on capital structure. Meanwhile, return on assets (ROA) has a negative and significant effect on capital structure. Meanwhile, the simultaneous influence of firm size, tangibility, liquidity, return on assets (ROA) and return on equity (ROE) has a positive and significant effect on capital structure. The amount of influence caused is 30.0 percent. The rest of 0.700 or 70.0 percent is explained by other variables.Keywords: Company Size, Tangibility, Liquidity, ROA, ROE, Capital Structure